C-Peptide and Atherogenesis: C-Peptide as a Mediator of Lesion Development in Patients with Type 2 Diabetes Mellitus?. (1st April 2008) - Marx, Nikolaus; Walcher, Daniel
Abstract : Patients with insulin resistance and early type 2 diabetes exhibit an increased propensity to develop a diffuse and extensive pattern of arteriosclerosis. Typically, these patients show increased levels of C-peptide and over the last years various groups examined the effect of C-peptide in vascular cells as well as its potential role in lesion development. While some studies demonstrated beneficial effects of C-peptide, for example, by showing an inhibition of smooth muscle cell proliferation, others suggested proatherogenic mechanisms in patients with type 2 diabetes. Among them, C-peptide may facilitate the recruitment of inflammatory cells into early lesions and promote lesion progression by inducing smooth muscle cell proliferation. The following review will summarize the effects of C-peptide in vascular cells and discuss the potential role of C-peptide in atherogenesis in patients with type 2 diabetes.